Strategi Meningkatkan Kreativitas Siswa Melalui Model Project Based Learning (PjBL) - Harjun Harjun; Jumatin Jumatin; Yuniarti Ahiri; Juwantho Lewa (Indo Publishing, 2026)
Student creativity is one of the essential competencies that must be developed in 21st-century learning to foster learners who are innovative, adaptive, and capable of solving problems contextually. However, various studies indicate that learning processes in schools remain predominantly teacher-centered and provide limited opportunities for students to optimally develop creative thinking skills. This study aims to analyze effective learning strategies for enhancing student creativity across different educational levels through a library research approach. The review was conducted through stages of planning, data collection, and analysis by examining 20 scholarly articles published between 2020 and 2025 and obtained from academic databases such as Google Scholar, Garuda, and SINTA-indexed journals. The findings reveal that innovative learning strategies, particularly Project Based Learning (PjBL), consistently improve student creativity, as reflected in increased ability to generate diverse ideas, think flexibly, and produce original and meaningful work. In addition to PjBL, STEM/STEAM approaches, technology-based learning, differentiated instruction, and the integration of local wisdom have also been shown to contribute positively to the development of student creativity. Nevertheless, the implementation of these strategies faces challenges, including limited time, inadequate facilities, teacher readiness, and varying levels of student participation. Therefore, this study recommends strengthening teacher competencies through continuous professional development, integrating educational technology, and developing evaluation systems that emphasize creative thinking processes. The results of this review are expected to serve as a reference for educators in designing innovative learning practices that are responsive to the demands of 21st-century education.